Kepemimpinan Kyai sebagai Kunci Motivasi Santri Kalong di Pesantren: Sebuah Studi Kasus - Maulana, Fatkhurrozak Johan; Ernawati, Fetty (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The purpose of this study is to explain the types of leadership implemented at the Al-Munawwir Islamic Boarding School, Gipa al-Qasim Complex, Sewon Bantul, and how this leadership motivates students to memorize the Qur’an.Method – This research employs a qualitative approach with data collection methods including interviews, documentation, and observation, as well as data analysis involving data reduction, data presentation, and drawing conclusions and verification. Data validity is tested using source and technique triangulation.Findings – The study reveals that the paternalistic and charismatic leadership of the Kyai significantly enhances the motivation of santri kalong in memorizing the Qur'an. The reciprocal relationship between the Kyai and the santri fosters respect and a desire for blessings, with the Kyai's advice and exemplary behavior positively influencing the santri's motivation and Islamic character. The use of the sorogan method for evaluating memorization improves both the quantity and fluency of recitation, encouraging continuous review. These findings highlight the crucial role of leadership style in motivating santri. The study also emphasizes the need to improve communication between santri kalong and the Kyai and addresses challenges like the imbalance in study time and lack of commitment among non-resident santri. Despite these challenges, the Kyai's leadership proves vital in motivating santri kalong, significantly impacting their progress in Qur'an memorization. Research Implications – The implications of this research include educational learning, leadership development, educational policy. The study highlights the importance of the Kyai’s role in shaping the character and motivation of santri in Islamic boarding schools.